ANALISIS INVESTASI PORTOFOLIO SAHAM PASAR MODAL SYARIAH DENGAN MODEL MARKOWITZ DAN MODEL INDEKS TUNGGAL - Anita Fajar Triwahyuni, - (2019)
This research was conducted to determine the optimal portfolio formed using the Markowitz Model and the Single Index Model. The population used is all shares included in the JII which amount to 30 shares. The sample selection technique uses purposive sampling method and obtained 22 shares as the research sample. The results of the analysis using the Markowitz Model produce 7 stocks that form the optimal portfolio and provide portfolio Return expectations of 0.0196 or 1.96% with a portfolio risk level of 0.0007 or 0.07%. While using the Single Index Model produces 8 stocks that form the optimal portfolio with an expected Return of 0.0379 or 3.79% and portfolio risk of 0.0147 or 1.47%.